Designing Specific Primers for Amplification and Quantitative Analysis of the GPR120 and PPARγ Genes - Ramin Lotfi; Farhad Salari (Research in Molecular Medicine)
Background: Designing the primer pairs is one of the most important factors in the amplification and quantitative analysis of the nucleic acid sequences of interest. Using in silico methods, the present study intends to design highly specific primers for quantitative analysis of the genes with minimum expression. To achieve this aim, we selected two candidate genes with little expression, namely, G-protein coupled receptor 120 (GPR120) and peroxisome proliferator-activated receptor-γ (PPARγ), in peripheral blood leukocytes of healthy volunteers. Methods: Peripheral blood was collected from 30 healthy volunteers. Primers for GPR120 and PPARγ were designed using online websites (UCSC, OligoCalc, and OligoAnalyzer) and the primer designing tool (NCBI). Total RNA extraction and cDNA synthesis were done using commercially available kits based on manufacturer instructions. Finally, the melting curve analysis of GPR120 and PPARγ was assessed using the quantitative real-time PCR method. Results: The in silico gene expression investigation revealed that GPR120 and PPARγ have minimal leukocyte expression. Besides, the melting curves analysis for both genes in the studied individuals showed only one melting peak, confirming the specific amplification of the desired genes. Conclusion: Altogether, the study findings indicated that we could utilize the peripheral blood sample for assessing the gene expression and amplification of omega-3 fatty acids receptors, i.e. GPR120 and PPARγ as two candidate genes with very low expression in leukocytes.